Milk Yield and Composition in Crossbred Cows as Influenced by Feeding Rumen Protected Protein and Fat - Mane, S. H.; Fulpagare, Y. G.; Deokar, D. K.; Kankhare, D. H.; Adangle, S. A. (Indian Journal of Animal Nutrition, 2018)
This study was undertaken to assess the effect of rumen-protected protein and fat on milk yield and composition in crossbred cows. Twenty four crossbred cows in 2nd to 4th lactation with most probable production ability of average 2300 L milk were divided into control (T0), protected protein (T1), protected fat (T2) and protected protein plus protected fat (T3) supplemented groups. Animals were fed from 30 daysprepartum to 90 days postpartum as per ICAR (1998). In groups T0 and T2 untreated groundnut cake (GNC) was included in the concentrate mixture whereas in groups T1 and T3, GNC was treated with formaldehyde (1 g/100 g CP). In addition, bypass fat (99%) was supplemented in groups T2 and T3 at 10 g/L milk production. The intakes of DM, DCP and TDN expressed on % BW basis were similar in all the groups. The average milk production during supplementation period was 9.82, 11.76, 11.41 and 12.43 kg/d in group T0, T1, T2 and T3, respectively which was higher (P